Interdisciplinary Integration of the Mother Tongue in the Primary Education System and its Importance - N. B. Adizova; S. U. Olimova (Researchparks Publishing, 2023)
In this article, the science of the mother tongue is related to which subjects in primary education, and views on its importance are stated.